Recovery from Obstetric Anal Sphincter Injury in a Prospective Cohort of First Births - Attanasio, Laura B.; Ranchoff, Brittany L.; Long, Jaime B.; Kjerulff, Kristen H. (American Journal of Perinatology, 2022)
Objective To identify risk factors for obstetric anal sphincter injuries (OASIS) for primiparous women who gave birth vaginally and to compare recovery by OASIS status in three domains as follows: (1) physical health and functioning, (2) mental health, and (3) healthcare utilization.Study Design This secondary analysis used data from 2,013 vaginal births in the First Baby Study, a prospective cohort study of women with first births between 2009 and 2011. Interview data at multiple time points were linked to birth certificate and hospital discharge data. The key exposure of interest was OASIS (3rd or 4th degree perineal laceration, identified in the hospital discharge data; n = 174) versus no OASIS (n = 1,839). We used multivariable logistic regression models to examine the association between OASIS and a range of outcomes including physical health and functioning, depression, and health care utilization, assessed at 1 month and 6 months postpartum.Results Eight percent of women had OASIS. In adjusted models, there were no differences in general physical health and functioning measures by OASIS (such as fatigue and overall self-rated health), but women with OASIS had higher rates of reporting perineal pain (p < 0.001), accidental stool loss (p = 0.001), and bowel problems (p < 0.001) at 1-month postpartum. By 6-month postpartum, there were no differences in reported physical health and functioning. There were no differences in probable depression at 1- or 6-month postpartum. Women with OASIS were more likely to attend a comprehensive postpartum visit, but there were no other differences in health care utilization by OASIS.Conclusion Women with OASIS were at increased risk of accidental stool loss, bowel problems, and perineal pain in the immediate postpartum period. Women who had OASIS had similar physical functioning across a range of general health outcomes to women who gave birth vaginally without OASIS.Key Points
Keywords: obstetric anal sphincter injury; perineal laceration; nulliparity; recovery; vaginal delivery